On the estimation of three parameters lognormal distribution based on fuzzy life time data - Shafiq, Muhammad; Alamgir,; Atif, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2016)
Countless statistical tools are available to extract information from data. Life time modeling is considered as one of the most prominent fields of statistics, which is evident from the developments made in this field in the last few decades. Almost every statistic for life time analysis is based on precise life time observations, however, life time is not a precise measurement but more or less fuzzy. Therefore, in addition to classical statistical tools, fuzzy number approaches to describe life time data are more suitable. In order to incorporate fuzziness of the observations, fuzzy estimators for the three parameter lognormal distribution were suggested. The proposed estimators cover stochastic variation as well as fuzziness of the observations.